Use of Information Resources in Tertiary Institutions Libraries in Adamawa State, Nigeria - BAPPAH , MAGAJI ABUBAKAR; DAHIRU, AISHATU BELLO (MiddleBelt Journal of Library and Information Science, 2020)
This study investigates the use of information resources in tertiary institutions libraries in Adamawa State, Nigeria. The objectives of the research were to identify the types of information resources provided in the tertiary institutions libraries, to identify the extent of satisfaction with the available information resources, as well as the challenges facing the use of information resources in the libraries. The study employed mixed research methodology. The twelve tertiary institutions libraries in Adamawa State were used for the study. The population of the study was 38,322 registered users. The simple random sampling technique was used to select 395respondents from the population. Self-developed questionnaire was used to collect data for the study. Findings from the study revealed that information resources such as references, periodicals, books and non-book materials were provided in the libraries. Most of the respondents used text book, journal and Internet. Additionally, several challenges hindering the use of information resources in the libraries under study were identified. The study recommended measures for overcoming the challenges that include among others the need for provision of more information resources as well adequate user orientation in the use of information resources.